Electrochemical Synthesis of Hybrid Layered Thermoelectric Materials Based on PEDOT/SnS Doped with Ag. Issue 23 (10th November 2021) - Serrano‐Claumarchirant, José F.; Igual‐Muñoz, Ana María; Culebras, Mario; Collins, Maurice N.; Cantarero, Andrés; Gómez, Clara M.
Abstract: Due to the increasing energy demand and public awareness of climate change and environmental problems, sustainable energy development has become one of the most strategic areas of research. In this work, a hybrid layered thermoelectric material is produced, which consists of the combination of poly(3, 4‐ethylenedioxythiophene) (PEDOT) and tin sulfide (SnS). The films are produced by the electrochemical deposition of SnS on the surface of a PEDOT electrode. The thermoelectric properties are optimized by controlling the doping level of SnS by adding Ag. As a consequence, the power factor is remarkably improved up to 58.6 µW m –1 K –2, which is more than two orders of magnitude higher than that of the undoped materials. Abstract : Synthesis of hybrid layered thermoelectric materials by combining the electrochemical synthesis of poly (3, 4‐ethylenedioxythiopehe) (PEDOT) and tin sulfide (SnS) with silver doping optimization results in new flexible materials, environmentally friendly and with a remarkably improved power factor (58.6 µW m –1 K –2 ). This is more than two orders of magnitude higher than the undoped materials.